Revision of the genus Paraspicera Kieffer, 1907 (Hym: Figitidae: Aspicerinae) - Ros-Farré, P.; Pujade-Villar, J. (Zootaxa, 2011)
Paraspicera Kieffer, 1907 is a genus of Aspicerinae (Hymenoptera: Cynipoidea: Figitidae) of Nearctic distribution that includes a small number of species. The diagnostic characters to differentiate Paraspicera from other similar genera are described. From the five known species of Paraspicera only P. bakeri Kieffer, 1907 belongs to Paraspicera; the other species are transferred to the genus Aspicera Dahlbom, 1842: A. clarimontis Kieffer rev. status, A. uthaensis Ashmead rev. status, A. foveata (Belizin) n. comb., and A. kerzhneri (Kovalev) n. comb. Paraspicera bakeri is redescribed and a new species is described: P. brandaoi n. sp. The diagnostic characters of both species are illustrated. The genus Heteraspidia Belizin, 1952 is synonymyzed with Aspicera.